Tinjauan Yuridis Peran dan Tanggung Jawab PPATK Sebagai Intelegency Unit dalam Mencegah Tindak Pidana Money Laundering - I Kade Juniana; Anak Agung Sagung Laksmi Dewi; Made Minggu Widyantara (Jurnal Analogi Hukum, 2022)
The issues raised in this study include the legal arrangements of PPATK as a unit of Indonesian Financial Intelligence and the roles and responsibilities of PPATK to prevent money laundering in the banking system in Indonesia. The writing of this thesis uses the research method of collecting normative literature data (library research) along with collecting data and reading references through regulations, the internet and other sources, then selecting the appropriate data to support the writing. The result of this study is that PPATK as an agency established for the prevention and eradication of money laundering crimes has been extended with the enactment of Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering. One of them is PPATK to temporarily suspend suspicious financial transactions. PPATK plays a role in maintaining financial system stability, especially the Indonesian economic system and is responsible for efforts to eradicate money laundering in the banking system in Indonesia.